Effectiveness Implementation Electronic Land Certificates In Preventing Land Mafia Practices - Samad, Mutmainna; Bachmid, Fahri; Handayani, Dwi (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to examine and explain the effectiveness of implementing electronic land certificates in preventing land mafia practices, the factors influencing it, and to investigate the application of electronic land certificates in Pinrang Regency. The research employs an empirical legal research method, with the study conducted at the ATR/BPN Office in Pinrang Regency. Data were collected through interviews and literature studies, which were analyzed then qualitatively and descriptively. The findings indicate that the introduction of electronic land certificates significantly enhances transparency in land ownership, allowing the public easier access to information and thereby reducing the likelihood of fraud. Additionally, the study finds that a digitized and integrated land registration system can lead to a significant reduction in land disputes, particularly those triggered by land mafia activities. However, the research also highlights potential technical challenges and cybersecurity threats that could compromise the integrity of electronic certificates, emphasizing the need for robust security measures to protect against data breaches and fraud. Based on these findings, the study recommends the establishment of comprehensive cybersecurity protocols and public education initiatives to ensure that landowners and potential buyers can effectively verify the authenticity of electronic land certificates. Furthermore, it suggests that policymakers are prioritizing the digital transformation of land management systems to enhance efficiency and public participation in governance.